Effect of conservation agriculture and weed management on weeds, soil microbial activity and wheat (Triticum aestivum) productivity under a rice (Oryza sativa)-wheat cropping system - BAGHEL, JITESH KUMAR; DAS, T K; RAJ, RISHI; PAUL, SANGEETA; MUKHERJEE, IRANI; BISHT, MAMTA (The Indian Journal of Agricultural Sciences, 2018)
Field experiment was carried out during the winter seasons of 2012-13 and 2013-14 to evaluate the effects of conservation agriculture (CA) and weed management practices on weeds, soil microbial activity and wheat productivity under a CA-based three-year old rice (Oryza sativa L.) - wheat (Triticum aestivum L. emend Fiori & Paol.) rotation. The design was a split plot with CA practices adopted in main plots and weed control measures in sub-plots with three replications. Results showed that zero till wheat (ZTW) encountered comparatively lower weed infestations compared to conventional till wheat (CTW). The ZTW with rice residue under (DSR) + mungbean residue (MR) – ZTW + rice residue (RR) – zero till summer mungbean (ZTSMB) + wheat residue (WR) recorded 58.8% and 61.9% higher soil dehydrogenase activity (DHA) and 48.2% and 53.8% more microbial biomass carbon (MBC) during 2012-13 and 2013-14, respectively than CTW under TPR-CTW, but weed control/ herbicides applications did not significantly influence microbial activity. Wheat crop yield was higher in ZTW than CTW. Among the CA treatments, the directseeded rice (DSR) + mungbean residue (MR) – ZTW + rice residue (RR) – zero till summer mungbean (ZTSMB) + wheat residue (WR), and DSR – ZTW – ZTSMB resulted in higher values of yield attributes (spike no./m2, grain/ spike) and yield of wheat. The increase in wheat yield due to the DSR + MR – ZTW + RR –ZTSMB + WR was 17.9 and 18.4%, respectively in 2012-13 and 2013-14 over that in TPR–CTW. The sequential applications of preemergence pendimethalin 1.0 kg/ha at 2 days after sowing (DAS) and post-emergence sulfosulfuron 25 g/ha at 30 DAS resulted in an effective control of weeds, irrespective of zero till (ZT) and conventional till (CT) conditions and gave significantly higher yield attributes and yield of wheat. This study provides information on better soil microbial health and higher wheat productivity under CA practices compared to CT conditions through effective weed control in rice-wheat cropping system. The recommendation may be adopted in the Indo-Gangetic plains of India with similar climatic and edaphic conditions.